Molecular dynamics and experimental study on the adhesion mechanism of polyvinyl alcohol (PVA) fiber in alkali-activated slag/fly ash. (July 2021) - Zhang, Shizhe; Duque-Redondo, Eduardo; Kostiuchenko, Albina; Dolado, Jorge S.; Ye, Guang
Abstract: This paper aims to study the adhesion mechanism of polyvinyl alcohol (PVA) fiber within alkali-activated slag/fly ash (AASF) matrix using molecular dynamics (MD) simulation in combination with systematic experimental characterization. The adhesion of PVA to C-(N-)A-S-H gel with different Ca/(Si+Al) and Al/Si ratios was modeled using MD simulation, with the related adsorption enthalpy calculated and the adhesion mechanism explored. The experimentally attained chemical bonding energy of PVA fiber in AASF coincides well with the simulation results. In both cases, the adhesion enhances primarily with increasing Ca/(Si+Al) ratio of C-(N-)A-S-H gel. Additionally, MD simulation indicates preferential element distributions of Ca around PVA molecule, which was confirmed experimentally by the detection of the Ca-rich C-(N-)A-S-H gel in the interfacial transition zone (ITZ). This study provides further insights into the adhesion mechanism of PVA fiber to C-(N-)A-S-H gel formed in AASF, which is particularly valuable for the future development of PVA-based high-performance alkali-activated composites.